New Frontiers Law and Society in the Roman World - du Plessis, Paul J. (Edinburgh University Press, 2013)
Roman law as a field of study is rapidly evolving to reflect new perspectives and approaches in research. Scholars who work on the subject are increasingly being asked to conduct research in an interdisciplinary manner whereby Roman law is not merely seen as a set of abstract concepts devoid of any background, but as a body of law which operated in a specific social, economic and cultural context. This "context-based" approach to the study of Roman law is an exciting new field which legal historians must address. Since the mid-1960s, a new academic movement has advocated a "law and society" approach to the study of Roman law instead of the prevailing dogmatic methodology employed in many Faculties of law.